Vacuum drainage of tissues in treatment of inflammatory diseases of the maxillo-facial area and neck. - V. A. Malanchuk; A. V. Sidoryako; S. V. Sidoryako (Medičnì Perspektivi)
Objective of the study: to increase the efficiency of drainage of tissues with phlegmons of the maxillo-facial area and neck using vacuum drainage.The device was used in 55 people with phlegmons of the maxillo-facial area and neck, aged from 21 to 65 years in the maxillo-facial department of the City Clinical Hospital for Emergency and Medical Care, Zaporizhyzhya. The proposed device improves the efficiency of evacuation of exudate from the wound. The decrease in the number of complications, the occurrence of bedsores in the wound caused by tubular drainage is observed, it prevents the spread of the inflammatory process in the adjacent tissue spaces. The improvement of the clinical picture and stabilization of the general condition in 53 (96.4%) patients of the second group was noted on the 2.4±0.7 day after surgery, in 43 (95.6%) patients of the first group – on 3.7±0.6 day; the intensity of the pain syndrome decreased on average on 3.2±0.4 day. In 48 (87.3%) patients of the second group suppuration was absent already on 2.4±0.6 day, the formation of granulations – on 3.2±0.5 day, and complete cleansing and convergence of the wound edges – on 6.2±0.7 day. In 4 patients of the first and second groups, the healing time of the postoperative wound was longer: the cessation of suppuration was noticed on 6th-7th day, the appearance of granulations – on 7th-8th day, complete cleansing, and the marginal convergence of the wound – on 11.2±0.8th day р<0,001. Vacuum drainage accelerates the onset of the second phase of the inflammatory process, reduces the dynamics of the disease course  and the patient's recovery at least twice.